Medium-term results of transcatheter implantation of MedLab-CT aortic valve prosthesis - V. V. Bazylev; A. B. Voevodin; A. S. Shalygina (Российский кардиологический журнал)
Aim. To assess the clinical and hemodynamic results of transcatheter aortic valve replacement with the MedLab-CT prosthesis.Material and methods. MedLab-CT is the first Russian transcatheter implantable cardiac valve prosthesis. It is a balloon — an expandable stent, the cusps of which are made of 0,1 mm thick polytetrafluoroethylene plates. The use of synthetic material for the manufacture of the locking mechanism of the transcatheter implantable cardiac valve prostheses is a priority choice in the world. The reason was the hypothesis suggesting the absence of biodegradation of polytetrafluoroethylene in the body. The mechanical stability of the valve was tested on the pulse duplicator with a load equivalent to 10 years of functioning in the aortic position. The study included 69 patients who underwent implantation of the MedLab-CT prosthesis. One of the exclusion criteria for surviving patients was a follow-up period of less than 6 months. We estimated survival and incidence of clinically significant stroke, as well as hemodynamic parameters according to echocardiography for up to 3 years. Thirty nine patients were examined by face-toface approach, the rest ones underwent a telephone questionnaire survey.Results. The average follow-up was 9,6 months, the maximum — 3 years. Most patients belonged to the elderly group (average age 73,3 years). For 51 patients (74%) according to the EuroSCORE scale and for 37 (54%), according to the STS scale, a high risk of surgical intervention was determined: ≥8%.Mortality rate was 13% — 6 deaths were noted at the hospital stage, 3 patients died in the long term. No strokes recorded. In the face-to-face group, mean gradient on the aortic valve prosthesis was determined to be 8,41±4,21 mm Hg; insufficiency due to paraprosthetic fistulas not higher than I degree was observed in 7 patients (18%), not higher than II degree — in 1 patient; cases of transvalvular aortic insufficiency was not revealed.Conclusion. The results on the studied parameters are comparable with the data presented by foreign randomized clinical trials of imported models of transcatheter aortic valve prostheses.